The Influence of Word of Mouth (WOM) and Customer Relationship Management (CRM) on Customer Loyalty at PT Garuda Sertifikasi Indonesia with Customer Delight as a Mediating Variable - Putu Anom Wisnu Wisnawa; Anak Agung Putu Agung; I Nengah Suardhika (International Journal of Economics and Management Sciences, 2025)
The study aims to examine the influence of word of mouth (WOM) and customer relationship management (CRM) on customer loyalty at PT Garuda Sertifikasi Indonesia, with customer delight serving as a mediating variable. This research is motivated by the increasing competition among certification service providers, which requires companies to implement effective strategies to retain and satisfy their customers. The target population in this study encompasses the entire client base of PT Garuda Sertifikasi Indonesia, totaling 429 individuals. The sampling technique used was Hair’s formula, resulting in 70 respondents. Data were collected through questionnaires, interviews, and documentation. A path analysis technique was used to analyze the data to determine direct and indirect effects between variables. The findings indicate that both WOM and CRM positively influence customer loyalty. Effective word-of-mouth strategies help build the company’s reputation and trust, while CRM ensures consistent communication, better service, and long-term customer engagement. The research also found that WOM and CRM positively affect customer delight. Customers who experience exceptional service and personalized attention tend to be more satisfied and emotionally connected to the brand. Furthermore, customer delight was proven to have a significant positive impact on customer loyalty. It also acts as a mediating variable, strengthening the effect of WOM and CRM on loyalty. This means that delighted customers are more likely to remain loyal and advocate for the company. The results of this study emphasize the importance of maintaining strong relationships and exceeding customer expectations in order to build sustainable loyalty. This research contributes valuable insights for service-based companies in enhancing marketing and customer retention strategies.